2022
DOI: 10.1109/lgrs.2021.3067727
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Phase Detrending for GNSS Scintillation Detection: A Case Study Over Antarctica

Abstract: We aim at contributing to the reliability of the phase scintillation index on Global Navigation Satellite System (GNSS) signals at high-latitude. To the scope, we leverage on a recently introduced detrending scheme based on the signal decomposition provided by the fast iterative filtering (FIF) technique. This detrending scheme has been demonstrated to enable a fine-tuning of the cutoff frequency for phase detrending used in the phase scintillation index definition. In a single case study based on Galileo data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 24 publications
1
39
1
Order By: Relevance
“…Authors found that the scintillation impact is strongest when the appearance of the PMAFs coincides with the appearance of the PCPs. Studies (Van der Meeren et al, 2016) showed that the Sun-aligned arc in the polar cap does not cause significant phase scintillations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors found that the scintillation impact is strongest when the appearance of the PMAFs coincides with the appearance of the PCPs. Studies (Van der Meeren et al, 2016) showed that the Sun-aligned arc in the polar cap does not cause significant phase scintillations.…”
Section: Introductionmentioning
confidence: 99%
“…During a strong and stable polar cap convection, segmentation may not happen, and a continuous tongue of ionization (TOI) may be formed across the polar cap (Foster et al, 2005). Phase scintillations in TOI were studied in the paper by Van der Meeren et al (2014), who was observed bursts of phase scintillations and no amplitude scintillations in relation to the leading gradient of the TOI. Patches may develop smaller-scale irregularities down to decametre scale through the Kelvin-Helmholtz (KH) and gradient drift instabilities (Oksavik et al, 2012;Clausen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study [11] revealed that there exist fluctuations that are refractive in nature that can mimic phase scintillations, while [10] showed that dominant phase variations in the polar and auroral regions are indeed refractive. Recently, studies [12,13] also emphasized the importance of proper detrending in the identification of scintillation in the polar region.…”
Section: Introductionmentioning
confidence: 99%
“…Amplitude scintillation occurrence in the polar region is very low due to the nature of the scintillation producing irregularities [37]. It is compounded by completed dominance of phase variations due to the problems with the detrending of the phase of the GNSS signal [12,13] to determine the phase scintillation index. However, the introduction of the new dynamic detrending and method along with the calculation of the modified scintillation method [38] provided an opportunity to detect amplitude scintillation occurrence accurately.…”
Section: Introductionmentioning
confidence: 99%